Fossil Ants (Hymenoptera: Formicidae) of the Middle Eocene Kishenehn Formation - Lapolla, John S; Greenwalt, Dale E (Sociobiology, 2015)
A broad range of interesting fossil insects have been discovered recently in Kishenehn Formation shale (middle Eocene, ca. 46 myo) in northwestern Montana, among them a diversity of ant species. Two hundred forty-nine ant fossils were examined in this study, with 152 them assignable at least to subfamily. Here, twelve fossil ant species are formally described. These include a new genus of Dolichoderinae (Ktunaxia, gen. nov.), and the oldest known species from two extant genera: Crematogaster (C. aurora, sp. nov.) and Pseudomyrmex (P. saxulum, sp. nov.). The Eocene is of particular interest for understanding ant evolution because it is during this period that many present-day speciose and ecologically dominant clades of ants apparently emerged. In order to understand the evolution of ants, and in particular their march to the terrestrial dominance observed in modern times, it is critical to understand the tempo of ant diversity during the Eocene. The Kishenehn provides another window into Eocene ant diversity; its relevance to some of the other major Eocene ant fossil deposits is discussed.